Dehydration kinetics of Musa acuminata in osmotics and microwave drying. (2017) - Selvi, N. Josephine; Baskar, G.; Singh, Aruna
To develop a product, banana chips of high consumer acceptability, the banana slices of 2 mm thickness were first osmotically pretreated and then convectively dried in oven at constant air temperature of 40°C to safe moisture level followed by microwave drying. Different experimental combinations of osmotic process parameters, i.e., palm sugar concentration, solution temperature and immersion time is to be tried using Box-Behnken design of experiments. Response surface methodology has to be used to investigate the effect of sugar concentration (40-45°Brix), solution temperature (40-60°C), and immersion time (30-150 min) on the water loss and solute gain. The experimental data was fitted to different empirical kinetic models including Peleg, Page and Midilli equations. Determination of coefficient (R 2 ), root mean square error and mean relative deviation modulus were used for determination of the best suitable model. The present work shows that the Peleg empirical model satisfactorily described the dehydration kinetics for osmotic dehydration where as page and Midilli for microwave drying.